Registry of the Spanish Network for Systemic Sclerosis: Survival, Prognostic Factors, and Causes of Death. Issue 43 (October 2015) - Simeón-Aznar, C.P.; Fonollosa-Plá, V.; Tolosa-Vilella, Carles; Espinosa-Garriga, G.; Campillo-Grau, M.; Ramos-Casals, M.; García-Hernández, F.J.; Castillo-Palma, M.J.; Sánchez-Román, J.; Callejas-Rubio, J.L.; Ortego-Centeno, N.; Egurbide-Arberas, M.V.; et al.
Abstract : Abstract: Systemic sclerosis (SSc) is a rare, multisystem disease showing a large individual variability in disease progression and prognosis. In the present study, we assess survival, causes of death, and risk factors of mortality in a large series of Spanish SSc patients. Consecutive SSc patients fulfilling criteria of the classification by LeRoy were recruited in the survey. Kaplan–Meier and Cox proportional-hazards models were used to analyze survival and to identify predictors of mortality. Among 879 consecutive patients, 138 (15.7%) deaths were registered. Seventy-six out of 138 (55%) deceased patients were due to causes attributed to SSc, and pulmonary hypertension (PH) was the leading cause in 23 (16.6%) patients. Survival rates were 96%, 93%, 83%, and 73% at 5, 10, 20, and 30 years after the first symptom, respectively. Survival rates for diffuse cutaneous SSc (dcSSc) and limited cutaneous SSc were 91%, 86%, 64%, and 39%; and 97%, 95%, 85%, and 81% at 5, 10, 20, and 30 years, respectively (log-rank: 67.63, P  < 0.0001). The dcSSc subset, male sex, age at disease onset older than 65 years, digital ulcers, interstitial lung disease (ILD), PH, heart involvement, scleroderma renal crisis (SRC), presence of antitopoisomerase I and absence of anticentromere antibodies, and active capillaroscopic pattern showed reduced survival rate. In a multivariate analysis, older age at disease onset, dcSSc, ILD, PH, and SRC were independent risk factors for mortality. In the present study involving a large cohort of SSc patients, a high prevalence of disease-related causes of death was demonstrated. Older age at disease onset, dcSSc, ILD, PH, and SRC were identified as independent prognostic factors.